Structural Consequences of Copper Binding to the Prion Protein - Giulia Salzano; Gabriele Giachin; Giuseppe Legname (Cells, 2019)
Prion, or PrPSc, is the pathological isoform of the cellular prion protein (PrPC) and it is the etiological agent of transmissible spongiform encephalopathies (TSE) affecting humans and animal species. The most relevant function of PrPC is its ability to bind copper ions through its flexible N-terminal moiety. This review includes an overview of the structure and function of PrPC with a focus on its ability to bind copper ions. The state-of-the-art of the role of copper in both PrPC physiology and in prion pathogenesis is also discussed. Finally, we describe the structural consequences of copper binding to the PrPC structure.